Implementation of a Symmetric Chaotic Encryption Scheme - Sivanandan, Easwari (Universiti Teknologi Petronas, 2004)
Voice over Internet Protocol technology (VoIP) is progressing commendably, but packet loss, propagation delay, jitter, unreliable IP networks, and vulnerability to attacks by Internet hackers are among critical issues that have been identified. Voice privacy and security needs to focused upon and data encryption techniques are the answers in providing the security needed. However, traditional cryptosystems demand high computational complexity andhigh digital signal processors which in return increases the cost of implementation. There is parallel growth in cryptographic techniques which originated anintense research activity and the search for new directions in cryptography such as chaotic encryption. Due to its deterministic nature and its sensitivity to initial conditions, chaos has a certain potential in creating a newway of securing information to be transmitted or stored. There are two main objectives to this project. First is study the feasibility of the chaotic encryption scheme in providing a solution in to preserve data security while maintaining the voice quality for voice over Internet Protocol. Secondly, a new scheme based on a chaos system will be implemented for voice data. In order to achieve the second objective, a study had been carried out on other proposed schemes mainly the Hierarchical Data Security Protection (HDSP) for VoIP. This scheme performs two main operations which is the data-frame interleaving and intra-frame data encryption using bit swapping. Based onthe HDSP scheme, the author suggests a new scheme using two level encryption techniques, based on chaos. In this scheme, the author uses the bit swapping technique as the second encryption-decryption level and enhances it with a first level encryption-decryption scheme using the two's compliment overflow nonlinearity encoder-decoder pair. The implementation ofthis scheme is specified to do real time processing ofvoice data. It can also be used to read, encrypt and write a wave file. The entire system is implemented, tested and validated using MATLAB and Visual C++. Due to the promising prospect ofchaotic encryption in the field ofcryptography, and the lack ofimplementation ofthis new encryption-decryption algorithm, this project focuses on introducing a new symmetric encryption-decryption scheme based on a chaos system for VoIP.